Role of Pore Microstructures on the Decomposition Kinetics in MAX-Phase Composites - Low, It Meng; Pang, W. (Asian-Australasian Association for Composite Materials (AACM), 2012)
In this paper, the role of pore microstructures on the susceptibility of MAX- phase composites to thermal dissociation at 1300-1800 °C in high vacuum has been studied using in-situ neutron diffraction. Positive activation energies were determined for the decomposition of MAX phases except for Ti3AlC2 where negative activation energy of 71.9 kJ mol-1 was obtained due to formation of fine pores on TiCx. An Avrami exponent (n) of < 1.0 was determined, indicative of the highly restricted diffusion of Al or Si between the channels of M6X octohedra. The pore microstructure of decomposed MAX phase has been shown to play a vital role in the kinetics of decomposition with coarse-pores facilitating the decomposition process but the fine-pores hindering it.